Type IV Esophageal Atresia with Nasogastric Tube in Stomach - Lloreda-García, Jose María; Sevilla-Denia, Sandra; Leante-Castellanos, Jose Luis; Fuentes-Gutiérrez, Carmen (Journal of Neonatal Surgery, 2017)
Please see fulltext.